The Impact of Fluid Overload on Outcomes in Children Treated With Extracorporeal Membrane Oxygenation: A Multicenter Retrospective Cohort Study*. Issue 12 (December 2017) - Selewski, David T.; Askenazi, David J.; Bridges, Brian C.; Cooper, David S.; Fleming, Geoffrey M.; Paden, Matthew L.; Verway, Mark; Sahay, Rashmi; King, Eileen; Zappitelli, Michael
Abstract : Objective: To characterize the epidemiology of fluid overload and its association with mortality and duration of extracorporeal membrane oxygenation in children treated with extracorporeal membrane oxygenation. Design: Retrospective cohort study. Setting: Six tertiary children's hospital ICUs. Patients: Seven hundred fifty-six children younger than 18 years old treated with extracorporeal membrane oxygenation for greater than or equal to 24 hours from January 1, 2007, to December 31, 2011. Interventions: None. Measurements and Main Results: Overall survival to extracorporeal membrane oxygenation decannulation and hospital discharge was 74.9% ( n = 566) and 57.7% ( n = 436), respectively. Median fluid overload at extracorporeal membrane oxygenation initiation was 8.8% (interquartile range, 0.3–19.2), and it differed between hospital survivors and non survival, though not between extracorporeal membrane oxygenation survivors and non survivors. Median peak fluid overload on extracorporeal membrane oxygenation was 30.9% (interquartile range, 15.4–54.8). During extracorporeal membrane oxygenation, 84.8% had a peak fluid overload greater than or equal to 10%; 67.2% of patients had a peak fluid overload of greater than or equal to 20% and 29% of patients had a peak fluid overload of greater than or equal to 50%. The median peak fluid overload was lower in patients who survived on extracorporeal membrane oxygenation (27.2% vs 44.4%; p < 0.0001) and survived to hospital discharge (24.8% vs 43.3%; p < 0.0001). After adjusting for acute kidney injury, pH at extracorporeal membrane oxygenation initiation, nonrenal complications, extracorporeal membrane oxygenation mode, support type, center and patient age, the degree of fluid overload at extracorporeal membrane oxygenation initiation ( p = 0.05), and the peak fluid overload on extracorporeal membrane oxygenation ( p < 0.0001) predicted duration of extracorporeal membrane oxygenation in survivors. Multivariable analysis showed that peak fluid overload on extracorporeal membrane oxygenation (adjusted odds ratio, 1.09; 95% CI, 1.04–1.15) predicted mortality on extracorporeal membrane oxygenation; fluid overload at extracorporeal membrane oxygenation initiation (adjusted odds ratio, 1.13; 95% CI, 1.05–1.22) and peak fluid overload (adjusted odds ratio, 1.18; 95% CI, 1.12–1.24) both predicted hospital morality. Conclusions: Fluid overload occurs commonly and is independently associated with adverse outcomes including increased mortality and increased duration of extracorporeal membrane oxygenation in a broad pediatric extracorporeal membrane oxygenation population. These results suggest that fluid overload is a potential target for intervention to improve outcomes in children on extracorporeal membrane oxygenation. Abstract : Supplemental Digital Content is available in the text.